Analisis Perbedaan Kinerja Keuangan Perusahaan Sebelum Dan Sesudah Merger (Kasus Pada Bank CIMB Niaga Yang Terdaftar Di BEI) - Hapsari, Suciati, Dra. Wuryaningsih DL, MM (2016)
This study aims to determine differences in the company's financial performance before and after the merger case at Bank CIMB Niaga is listed on the Stock Exchange. The population in this study are all banking companies have merged. The samples are Bank CIMB Niaga. Techniques used in the sampling technique is purposive sample. This study analyzed using an analysis tool Du Pont System. To test differences in financial performance using Independent Sample T-tests and Pired Sample T-test. Before the test the difference in the two values on average, first tested for normality using the Kolmogorov-Smirnov Z, whereas for the test authors homogeneous variance using the F test, in which the two tests was conducted using SPSS application. The results using Independent Sample T-test, there is one variable Financial Leverage Multiplier (FLM) has improved. While the variable Total Return On Assets (ROA), Return on Equity (ROE), Total Assets Turn Over (TATO), Net Profit Margin (NPM) Not experienced the difference after being merged. Keywords: Du Pont, Financial Performance, Mergers, Banks.